Optimization of Nutrient Medium Composition for Entomopathogens Bacillus Thuringiensis Cultivation (Global Journal of Science Frontier Research, 2019)
The objective of the research was to develop an optimal liquid medium composition for bacteria strain Bacillus thuringiensis 87/3 which are the most favorable for the identifying the potential production of biologically active components. In this work we have used new entomopathogenic bacteria strain Bacillus thuringiensis var. thuringiensis (Bt H1) №87/3 selected in vitro, isolated from the larvae of leaf-eating insects natural populations of Leptinotarsa decemlineata Say (L4). Nutrient medium for cultivation of Bt 87/3 was optimized by a full-fledged experiment, according to the Box-Behnken (33) plan. Optimum concentrations were investigated in the medium of carbon source (15 g/l of glucose), nitrogen (10 g/l of corn extract) and content of phosphorus-containing inorganic salts (1,5 g/l of diammonium phosphate). When growing this strain in periodic conditions at 30°C, the number of viable cells reached 4,4×109 cells/ml. The nutrient medium that was optimized can be recommended for the cultivation of Bacillus thuringiensis 87/3 in production conditions.
Keywords: bacillus thuringiensis; spore-crystal complex; cultivation; nutrient medium optimization; entomocidal effect; biocontrol